Environmental materials and waste : resource recovery and pollution prevention - Prasad, M. N. V. (Majeti Narasimha Vara), 1953-; Shih, Kaimin (London : Academic Press, an imprint of Elsevier, 2016)
Environmental Materials and Waste: Resource Recovery and Pollution Prevention contains the latest information on environmental sustainability as a wide variety of natural resources are increasingly being exploited to meet the demands of a worldwide growing population and economy. These raw materials cannot, or can only partially, be substituted by renewable resources within the next few decades. As such, the efficient recovery and processing of mineral and energy resources, as well as recycling such resources, is now of significant importance. The book takes a multidisciplinary approach to fully realize the number of by-products which can be remanufactured, providing the foundation needed across disciplines to tackle this issue. As awareness and opportunities to recover valuable resources from process and bleed streams is gaining interest, sustainable recovery of environmental materials, including wastewater, offers tremendous opportunity to combine profitable and sustainable production.
Note continued: 27.6.1. Enhanced Bioprocess Phosphorus Removal / R. Karunanithi / A. Szogi / N.S. Bolan / B. Seshadri / Y.S. Ok / S. Krishnamurthy / R. Naidu -- 27.6.2. Precipitation / A. Szogi / N.S. Bolan / R. Naidu / R. Karunanithi / S. Krishnamurthy / B. Seshadri / Y.S. Ok -- 27.6.3. Recovery of Phosphorus as Magnesium Ammonium Phosphate (Struvite) / R. Karunanithi / A. Szogi / N.S. Bolan / B. Seshadri / Y.S. Ok / S. Krishnamurthy / R. Naidu -- 27.6.4. Struvite Recovery From Effluent / R. Karunanithi / A. Szogi / N.S. Bolan / B. Seshadri / Y.S. Ok / S. Krishnamurthy / R. Naidu -- 27.6.5. Recovery of Phosphate as Calcium Phosphate / R. Karunanithi / A. Szogi / N.S. Bolan / B. Seshadri / Y.S. Ok / S. Krishnamurthy / R. Naidu -- 27.6.6. Calcium Phosphate Recovery From Effluents / R. Karunanithi / A. Szogi / N.S. Bolan / B. Seshadri / Y.S. Ok / S. Krishnamurthy / R. Naidu.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed April 26, 2016).
Keywords: Refuse and refuse disposal -- Environmental aspects; Recycling (Waste, etc.); Bioremediation; Pollution prevention; TECHNOLOGY & ENGINEERING -- Environmental -- General; Bioremediation; Pollution prevention; Recycling (Waste, etc.); Refuse and refuse disposal -- Environmental aspects; Electronic books